2017
DOI: 10.1002/ejhf.942
|View full text |Cite
|
Sign up to set email alerts
|

Immune mechanisms in heart failure

Abstract: Elevated levels of circulating pro-inflammatory biomarkers in patients with both ischaemic and non-ischaemic heart failure (HF) correlate with disease severity and prognosis. Experimental studies have shown activation of immune response mechanisms in the heart to provoke cardiac adverse remodelling and cause left ventricular dysfunction. Consequently, most of the clinical trials targeting elements of the immune response in HF attempted to modulate the inflammatory response. Surprisingly, clinical studies targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
147
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(160 citation statements)
references
References 127 publications
5
147
0
8
Order By: Relevance
“…Inflammation has a central role in the pathophysiology of heart failure (HF) . Interleukin (IL)‐6 is an important inflammatory mediator and might constitute a potential pharmacologic target in HF.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation has a central role in the pathophysiology of heart failure (HF) . Interleukin (IL)‐6 is an important inflammatory mediator and might constitute a potential pharmacologic target in HF.…”
Section: Biomarkersmentioning
confidence: 99%
“…Inflammation has a central role in the pathophysiology of heart failure (HF). 3 Interleukin (IL)-6 is an important inflammatory mediator and might constitute a potential pharmacologic target in HF. IL-6 was measured in patients from the A systems BIOlogy Study to TAilored Treatment in Chronic HF (BIOSTAT-CHF) cohort.…”
Section: Interleukin-6mentioning
confidence: 99%
“…Damage to these and other cell populations can release "danger signals" that trigger inflammatory processes and activate immune cells [18,19]. Inflammation, however, can also contribute to heart homeostasis by promoting tissue remodeling and removing damaged tissue from sites of injury [20,21]. Further complicating this picture, RT can directly affect immune cells, with the effects of cardiac radiation varying dramatically between cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some advances in diagnosis and therapy, the prognosis in patients with non‐ischaemic cardiomyopathy remains poor. Chronic low‐grade activation of the innate immune system with increased levels of inflammatory proteins, cytokines, and chemokines has been described in patients with HF . While it has been reported that activation of the immune system is associated with beneficial effects during cardiac regeneration, long‐term immune activation is also known to promote myocardial inflammation, which causes cardiac fibrosis and, thus, progression of HF .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic low-grade activation of the innate immune system with increased levels of inflammatory proteins, cytokines, and chemokines has been described in patients with HF. [3][4][5][6] While it has been reported that activation of the immune system is associated with beneficial effects during cardiac regeneration, 5,6 long-term immune activation is also known to promote myocardial inflammation, which causes cardiac fibrosis and, thus, progression of HF. 7 Among other mechanisms, infiltration with inflammatory cells mediates an increase of pro-inflammatory proteins in the myocardial tissue followed by myofibroblast activation, accumulation of extracellular matrix proteins, and cardiac remodelling.…”
Section: Introductionmentioning
confidence: 99%